COVID-19 pandemic and Romanian stock market volatility: A GARCH approach - Ștefan Cristian Gherghina; Daniel Ștefan Armeanu; Camelia Cătălina Joldeș (Journal of Risk and Financial Management, 2021)
This paper investigates the volatility of daily returns on the Romanian stock market between January 2020 and April 2021. Volatility is analyzed by means of the representative index for Bucharest Stock Exchange (BSE), namely, the Bucharest Exchange Trading (BET) index, along with twelve companies traded on BSE. The quantitative investigation was performed using GARCH approach. In the survey, the GARCH model (1,1) was applied to explore the volatility of the BET and BSE traded shares. Conditional volatility for the daily return series showed noticeable evidence of volatility that shifts over the explored period. In the first quarter of 2020, the Romanian equity market volatility increased to a level very close to that recorded during the global financial crisis of 2007-2009. Over the next two quarters, volatility had a downward trend. Besides, after VAR estimation, no causal connection was found among the COVID-19 variables and the BET index.
Keywords: 330; autocorrelation; COVID-19; GARCH models; Granger causality; Romanian stock market; vector autoregression model; volatility clustering